1998
DOI: 10.1590/s0100-879x1998000400011
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on esophageal motility

Abstract: It has been suggested that there are no gender effects on esophageal motility. However, in previous studies the subjects did not perform multiple swallows and the quantitative features of esophageal contractions were not evaluated. In order to investigate the gender effects on esophageal motility we studied 40 healthy normal volunteers, 20 men aged 37 ± 15 years (mean ± SD), and 20 women aged 38 ± 14 years. We used the manometric method with an eight-lumen polyvinyl catheter and continuous perfusion. The upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 13 publications
2
26
1
8
Order By: Relevance
“…A hipótese é que homens e mulheres têm diferenças na motilidade do esôfago. Métodos -Manometria de alta resolução foi realizada em voluntários saudáveis, 10 homens [média de idade: 37,7 (8,1) anos] e 12 mulheres [média de idade: 38,7 (7,5) anos], na posição sentada e com 10 deglutições de 5 mL de solução salina. Foram avaliadas a pressão integrada de relaxamento do esfíncter inferior do esôfago, velocidade da contração peristáltica, integral da contração distal, latência distal, extensão da contração proximal, duração da contração proximal >30 mmHg, duração da contração proximal, integral da contração proximal, pressão máxima do esfíncter superior do esôfago.…”
Section: Author' Contributionsunclassified
See 1 more Smart Citation
“…A hipótese é que homens e mulheres têm diferenças na motilidade do esôfago. Métodos -Manometria de alta resolução foi realizada em voluntários saudáveis, 10 homens [média de idade: 37,7 (8,1) anos] e 12 mulheres [média de idade: 38,7 (7,5) anos], na posição sentada e com 10 deglutições de 5 mL de solução salina. Foram avaliadas a pressão integrada de relaxamento do esfíncter inferior do esôfago, velocidade da contração peristáltica, integral da contração distal, latência distal, extensão da contração proximal, duração da contração proximal >30 mmHg, duração da contração proximal, integral da contração proximal, pressão máxima do esfíncter superior do esôfago.…”
Section: Author' Contributionsunclassified
“…The investigations about gender influence on esophageal motility have described that: integrated relaxation pressure of the lower esophageal sphincter (LES) is higher in women than in men (11) ; contractions in proximal esophagus have a higher area under the curve in women (7) ; women have an increase in contraction duration in distal esophagus (8) ; women have a higher LES pressure, higher distal amplitude, longer distal contraction duration and slower distal velocity of peristaltic contraction (14) . Gender does not influence whether esophageal motility is normal, spastic or with a non-specific motor disorder (1) .…”
Section: Introductionmentioning
confidence: 99%
“…We observed previously a difference between women and men in the contractility of the distal esophageal body (6) , which exclusively contains smooth muscle (14) . In this paper we described similar results in the proximal esophageal body, where there is striated muscle in the cranial part of both longitudinal and circular muscle layers that is gradually replaced by smooth muscle cells caudally (14) .…”
Section: -Out/dez 2009mentioning
confidence: 86%
“…Identidade de gênero. oropharyngeal transit (9) , UES opening duration (17,22) , pressure duration in the oropharynx with swallows (19) , duration of distal esophageal contractions (6) , and gastric emptying of solid food (13,15) . These results showed that women have a longer transit, contraction duration, UES opening and gastric emptying than men.…”
Section: -Out/dez 2009mentioning
confidence: 99%
See 1 more Smart Citation